Assiniboine Indian collection
Vocabulary list in the Assiniboine dialect with English equivalents and translations of the Lord's prayer and two poems. Dated 1886 July 1, McDougall Orphanage, Morley Mission, Alberta, Northwest Territories, Canada.
The Assiniboine (Stony) Indians are a part of the Dakota (Sioux) Indians.
Collection material in Assiniboine dialect, with English.
Forms part of: Miscellaneous Manuscripts collection.
Previously cataloged under Dakota Indians and prior to that under Sioux Indians.
Keywords: Lord's prayer; Assiniboine dialect -- Vocabulary; Assiniboine Indians -- Missions -- Alberta; Dakota Indians